Proton pump inhibitor use is associated with a variety of infections in patients with liver cirrhosis. Issue 50 (11th December 2020) - Labenz, Christian; Kostev, Karel; Galle, Peter R.; Wörns, Marcus-Alexander; Labenz, Joachim; Tanislav, Christian; Adarkwah, Charles Christian
Abstract : Abstract: There is evidence that intake of proton pump inhibitors (PPI) increases the risk for spontaneous bacterial peritonitis (SBP) in patients with liver cirrhosis. However, data regarding the impact of PPI intake on occurrence of infections other than SBP are still lacking. We hypothesized that PPI use is associated with a higher rate of infections other than SBP in patients with liver cirrhosis. The current case-control study sample included patients with liver cirrhosis from the Disease Analyzer database (IQVIA), which compiles data such as risk factors, drug prescriptions and diagnoses obtained from general practitioners and specialists in Germany. In total, 2, 823 patients with infections were matched with 2, 823 patients without infections by propensity scores. For quantification of PPI use the prescribed quantity of PPI during the past 12 months before index date was analyzed. Frequency of PPI users was significantly higher in patients with infections than in patients without infections (47.9% vs 37.9%). In regression analysis, PPI use was significantly associated with the occurrence of infections overall (OR 1.55, 95% CI 1.39–1.72, P < .001), and associated with the occurrence of lower respiratory tract infections, urinary tract infections and infectious gastroenteritis. There was no association between PPI use and skin infections. Pantoprazole and omeprazole were the most frequently prescribed PPIs and were both independently associated with the occurrence of infections. PPI use may be associated with infections other than SBP in patients with liver cirrhosis. Prescription of PPI should be limited to patients with a clear indication.